PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR ULANGAN HARIAN SISWA KELAS VIII PADA MATA PELAJARAN IPS EKONOMI DI SMP NEGERI 2 PURWANTORO TAHUN PELAJARAN 2012/2013. - Etik Setyowati (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2014)
Education will prepare the students to be smart people, useful for the country and nation. Because of the importance of the education, there are a lot of effort done by the government. To improve the quality of education in indonesia. As one of the institutions that hold a formal education, the school has a very important role in the realization of national education through the teaching and learning process. This research is quantitative. The population in this study were all students of class VIII. As a sample taken two classes is 64 students, the class of 32 students VIIIA. While as many as 32 students VIIIB class with the sampling technique is simple random sampling technique. Data collection techniques documentation of Economics Social Science teachers for learning outcomes data and the questionnaire method for data motivation. From the learning research that has been done can be concluded that, there are significant relationship between motivation to learn the daily tests student learning outcomes in social studies Economics at Junior High School eighth grade 2 Purwantoro school year 2012/2013. It is evident from the value of 6.363 Fcount while the value Ftable (3,996). On the other hand the value of Sighitung 0.000 and of Sigprob 0.05. This means that the value of Fcount ≥ Ftable (6.363> 3.996) and Sighitung ≤ Sigprob (0.05 ≤ 0.000). The amount of influence learning motivation on learning outcomes daily test eighth grade students at SMP Negeri 2 Purwantoro the Academic Year 2012/2013. Is showed with R Square = 0.522, which means that the learning outcomes are influenced by motivation by 52% and the remaining 48% influenced by other factors. While the results of the t test motivation factor positively impact on learning outcomes of daily tests in the eighth grade students of SMP Negeri 2 Purwantoro the Academic Year 2012/2013 is evident from the results of the analysis indicate tcount 9.717 ≥ ttable 2.000 or Sigcount ≤ Sigprob (0,000 ≤ 0,05). Thus, Ho is rejected and Ha accepted This suggests that there is the influence of motivation on learning outcomes of students' daily tests in social studies Economics at Junior High School eighth grade 2 Purwantoro school year 2012/2013. It means that the higher the child's motivation in learning the better of outcomes obtained.